Negosiasi Identitas Pasangan Perkawinan Beda Agama di Gereja Katolik - Viviana Ardine Mutiara K F; Turnomo Rahardjo; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Interfaith marriage is one of the paths taken by couples who undergo interfaith relationships. Globalization and technology allow people with various cultures to interact one another and allow individuals with different cultural backgrounds to be attracted, fall in love, and decide to marry. In the context of this study, the different identities brought by interfaith marriage couples in Catholic Church carry risks and challenges, so that interfaith marriage couples in Catholic Church negotiate their respective identities to get a communication experience that can be accepted, understood, appreciated, and achieve mutual comfort, through the relational identity that is formed. The purpose of this study is to find out how the experience of identity negotiations is carried out by interfaith marriage couples in Catholic Church. Several theories used to examine this phenomenon include Identity Negotiation Theory, Cultural Identity Theory, and Identity Management Theory. This research uses phenomenological approaches and focuses on the experiences of the couples and to explore more deeply of the things related to the experience in negotiating identity, the researcher uses data collection techniques through in-depth interviews. The results of this study, identity negotiations are carried out by interfaith marriage couples in Catholic Church to achieve a balance of identity and comfort in a joint relationship were successfully carried out. The couple succeeded in carrying out interfaith marriages in the Catholic Church while maintaining their respective religious identities and the couples succeeded in creating comfort in their relationship as interfaith marriage couples both in the family they built and in the surrounding community by supporting and respecting each other.